Kesan ketidakpastian persekitaran terhadap hubungan antara tadbir urus dan prestasi koperasi peladangan kelapa sawit di Malaysia - Mohd. Taufix A. Aziz; Norman Mohd. Saleh; Siti Faridah Abdul Jabbar; Noradiva Hamzah; Hayati Md Salleh (Penerbit Universiti Kebangsaan Malaysia, 2023)
Empirical studies on the influence of cooperative governance (TUK) on performance (PK) is scarce, especially involving the medium- and small-sized cooperatives. So far, past studies remain unclear and inconclusive on the existence of the relationship. The objective of this study is to investigate the existence of a relationship between TUK and PK and the moderating effect of the environmental uncertainty (KP) on the relationship between TUK and PK. This study anticipates that the implementation of TUK will affect PK depending on the context of cooperatives’ environment. The study used data sets of medium and small-sized cooperatives in the oil palm plantations industry in Malaysia. The results obtained from the PLS-SEM analysis confirmed that there was a positive and significant relationship between TUK and PK, while KP was found to have no moderating effect on the relationship. This study provides evidence on the effect of cooperative governance on cooperative performance regardless of the environment surrounding the cooperatives in Malaysia. All cooperatives should take seriously the importance of strengthening TUK to increase performance